Geothermal potential of granites: Case study- Kaymaz and Sivrihisar (Eskisehir region) Western Anatolia. (August 2022) - Chandrasekharam, Dornadula; Baba, Alper; Ayzit, Tolga; Singh, Hemant K.
Abstract: Radiogenic granites are gaining importance due to their ability to generate a substantial amount of electricity and support the advancement of agricultural and water sectors. In the western Anatolian region, such granites occupy a cumulative area of 6910 km 2 varying from 7 to 20 μW/m 3, far above the heat generated by the average continental crust of 5 μW/ m 3 . One cubic. The granite plutons of the Eskisehir region are amongst such granites with radioactive heat generation kilometer of such granite can generate 79 × 10 6  kWh of electricity. In the present case, the Eskisehir granites are capable of generating 616 million kWh of carbon-free electricity. Besides electricity, the heat from the granites can be utilized for space heating and greenhouse cultivation. This energy can also be utilized for the generation of fresh water from the sea through the desalination process. Hydrofracturing of the granites to create a fracture network connecting injection and production well is being replaced with closed-loop system that do not require knowledge about the stress pattern of the region and reduce the risk of induced micro-seismicity that was a bottleneck for developing EGS projects. Although the currently estimated cost of electricity generated from EGS projects is 9 euro cents/kWh, this cost will get reduced due to technological development in drilling technology. The Western Anatolian region has an additional advantage over the cost, since the drilling depth to capture the heat from the granites is shallow (∼3 km) which gives further benefit to the cost due to the reduction in drilling depth cost. In addition to high radiogenic granites, the presence of curie point temperature at shallow depth, high heat flow, and high geothermal gradient makes this region a warehouse of energy making Turkey energy-food and water independent in the future.